Metaphors of Identity and Alterity in Salman Rushdie’s The Ground Beneath Her Feet - Anton (Radu) Izabela-Daniela (Berpusi Publishing, 2023)
This article deals with some aspects of the English literature’s postcolonial background, looking at Salman Rushdie’s The Ground Beneath Her Feet from a cognitive linguistic perspective. At the same time, the paper aims at valorising the metaphors regarding “identity” and “alterity” within Rushdie’s literary discourse from his sixth novel. Although there has been a lot of research in this field there is still much to be discovered. Moreover, to date, there is no such analysis from a Cognitive linguistics point of view. Many researchers have been writing about Rushdie over the years, from different perspectives, but it seems there are no studies interested in discovering the writer’s options for figurative language in general, and especially the writer’s linguistic choices concerning “identity” and “alterity”.